Uzbekistan : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 1996)
This Selected Issues paper and Statistical Appendix analyzes developments in the domestic economy of Uzbekistan. The paper highlights that after declining by 17 1\2 percent during 1992-94, real GDP fell by only about 1 percent in 1995. The moderation in the output decline was due in part to a strong performance in the agricultural sector. Agricultural output grew by about 2 percent in 1995, owing to increases in grain production, while activity in the industrial, construction, transport, communications, and trade sectors continued to decline.